Concepts, challenges, and prospects on Multiagent Data Warehousing (MADWH) and Multiagent Data Mining (MADM). (21st February 2008) - Zhang, Wen-Ran
Multiagent Data Warehousing (MADWH) and Multiagent Data Mining (MADM) presents a multidimensional agent-oriented approach for brain modelling and decision making based on the hypothesis that a brain system consists of a society of semiautonomous neural agents and full autonomy is the result of coordination of semiautonomous functionalities. The agent-oriented approach leads to the following concepts, challenges, and prospects: agent laws, agentisation, agent discovery, law discovery, self-organisation, and reorganisation; mining agent association rules in 1st-order logic; modelling full autonomy as the result of coordination of semiautonomous agents; modelling evolving processes like growing and aging; modelling healthy states as well as unhealthy states of biological systems.